Agriculture Adaptation to Consequences of Global Climate Changes - D. G. Galkin (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
The goal of the article is to work out recommendations aimed at providing sustainability of agriculture development on the level of national economy in conditions of changing climate. The agriculture development within the frames of traditional approach can be studied in two aspects: as a sector subjected to the global climate change impact; as a sector promoting climate change due to greenhouse gas emission. The authors showed that in regard to present trends scientific recommendations aimed at agriculture adaptation to climate changes are the most significant for Russia. On the basis of provided concepts they identified key lines in the said adaptation: to develop innovation connected with adaptation to consequences of climate changes; to upgrade the system of agro-insurance; to use methods of organic food production; to monitor and appraise adaptation of agriculture to climate changes; to introduce strategic planning of sustainable development and location of agricultural production. These lines should be realized on the basis of integrity, strategic orientation and scientific support of agricultural production. These lines can stabilize the level of key parameters of the sector in the long-term perspective.